AKAL, WAHYU, DAN KASB MANUSIA MENURUT JABARIYAH DAN QADARIYAH - Edi Sumanto (Sekolah Pasca Sarjana IAIN Bengkulu, 2016)
Abstract: Reason, Revelation, And Human Efforts According to Jabarites And Qadarites. This article describes the views of Qadarites and Jabarites about the revelation, reason, and human efforts. The method used is based on a literature library from books, magazines and articles related. The study concluded: first, for Jabarites, reasoning has no meaning, because reasoning is of no use to humans, they are more dominant subject to revelation or the provision of God in their every activities, so human just only accept anything that has been given by The Creator. While according to Qadarites, Reasoning is to proportionate the provisions that God has made for man, to contribute to the act of doing, good or bad. In connection with the concept of revelation, for Jabarites that the revelation is a source of important and basic to those that must be followed, because the verses they are using is a verse to support the argument they use. While revelation in according to Qadarites is considered as to proportionate their opinion, because God disposes all human actions, but humans have a stake in it in order to try and select it.Finally, in Human efforts, for Jabarites that no efforts, because everything he does has been determined by God. There is no human power to do in doing something. however, according to Qadarites that human effort is depend on human beings themselves and the result depends according what he has done without any intervention from God.